Implementasi Penggunaan Media Pembelajaran Quizizz Sebagai Alat Penilaian Pemahaman Siswa Terhadap Mata Pelajaran - Hayati, Ridha Nurul; Farwati, Wiwik Wida; Alawiyah, Rosidah; Cahyani, Arie; Elthia, Memy Wardani (CV. Global Cendekia Inti, 2025)
This community service project aimed to enhance students' understanding and motivation in School subjects through the implementation of Quizizz, an interactive digital learning platform. The program was carried out at SDN 4 Banyumulek using a qualitative approach, including planning, implementation, and evaluation stages. The initial phase involved needs analysis and classroom observation, followed by Quizizz training and application in real-time learning settings. Data collection methods included observation, interviews, questionnaires, and documentation. Results showed that Quizizz successfully fostered student engagement, improved learning outcomes, and streamlined the assessment process by offering instant feedback and data analysis features. Most students achieved scores above the minimum competency standard (KKM), indicating that Quizizz is an effective and efficient tool for formative assessment. However, some technical challenges such as internet connectivity issues were noted. Overall, the integration of Quizizz into the learning process provided a positive impact on both teaching practices and student performance. It is recommended that educators adapt the use of this platform based on student needs and local context to ensure optimal learning outcomes.